Capital Account Convertibility : Review of Experience and Implications for IMF Policies - Evens, Owen.; Quirk, Peter (Washington, D.C. : International Monetary Fund, 1995)
The paper summarizes the main issues arising from experiences of industrial and developing countries with capital account liberalization and it examines the IMF's treatment of capital controls in its surveillance, use of IMF resources, and technical assistance activities. Case studies of recent experiences with capital controls in Chile, Colombia, Malaysia, and Venezuela are presented.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet